Microstructure and mechanical properties of manganese-alloyed austempered ductile iron produced by novel modified austempering process. Issue 1 (31st December 2022) - Hegde, Ananda; Sharma, Sathyashankara; Hande, Rajarama; B M, Gurumurthy
Abstract: Austempered ductile iron (ADI) has numerous applications because it is lightweight and has excellent mechanical properties. However, although the ADI obtained by the traditional austempering process possesses high strength and hardness, it has low toughness. To obtain superior mechanical properties for ADI, a modified austempering process is adopted. In this study, ADI is produced using a novel modified method with multi-stage austempering heat treatments. Various mechanical properties are determined to assess the relationship between heat treatment parameters and properties. Microstructural analysis is performed using scanning electron microscopy. The ADI produced using the aforementioned austempering process involving heat treatment at 420 °C is found to have the optimum combination of ultimate tensile strength and impact energy. Moreover, a higher nucleation rate is observed for samples supercooled at 260 °C over a short period.